Optimization of the photodynamic inactivation of prions by a phthalocyanine photosensitizer: The crucial involvement of singlet oxygen - Kostelanska, Marie; Freisleben, Jaroslav; Backovska Hanusova, Zdenka; Mosko, Tibor; Vik, Robert; Moravcova, Daniela; Hamacek, Ales; Mosinger, Jiri; Holada, Karel (Journal of biophotonics, 2019)
Prion disorders are fatal neurodegenerative diseases caused by the autocatalytic conversion of a natively occurring prion protein (PrPC ) into its misfolded infectious form (PrPTSE ). The proven resistance of PrPTSE to common disinfection procedures increases the risk of prion transmission in medical settings. Herein, we present the effective photodynamic inactivation (PDI) of prions by disulfonated hydroxyaluminum phthalocyanine (AlPcOH(SO3 )2 ) utilizing two custom-built red light sources. The treatment eliminates PrPTSE signal in infectious mouse brain homogenate with efficiency that depends on light intensity but has a low effect on the overall protein content. Importantly, singlet oxygen (O2 (1 Δg )) is the only species significantly photogenerated by AlPcOH(SO3 )2 , and it is responsible for the PDI of prions. More intensive light conditions show not only higher O2 (1 Δg ) production but also decreases in AlPcOH(SO3 )2 photostability. Our findings suggest that PDI by AlPcOH(SO3 )2 -generated O2 (1 Δg ) represents a promising approach for prion inactivation that may be useful in future decontamination strategies for delicate medical tools.
Keywords: Isoindoles; indoly; fotosenzibilizující látky; mozek; isoindoly; kyseliny sulfonové; prions; Indoles; Photosensitizing Agents; photodynamic inactivation; singletový kyslík; Prion Proteins; decontamination; fotochemoterapie; zvířata; myši; prionová bílkovina; Mice; Sulfonic Acids; singlet oxygen; Brain; phthalocyanines; Photochemotherapy; Animals; Singlet Oxygen